Methods Of Teaching The Technical Elements Of Football To Students Of Preschool Educational Organizations - Barno Pulatovna Abdullayeva (Euro Asian Journal Publishing, 2024)
the article deals with the methodology of teaching football in preschool institutions, which is more effective for the implementation of teaching the elements of football to preschoolers in order to ensure the implementation of measures on the development of football, which is currently relevant in our country. Advice and guidance on what to pay more attention to when teaching children football and how to organize classes
Keywords: football; children’s interests; game elements; training